The Distance to the Magellanic Stream: Constraints from Optical Absorption along Stellar Sight Lines - Sapna Mishra; Andrew J. Fox; J. V. Smoker; Scott Lucchini; Elena D’Onghia (The Astrophysical Journal)
The Magellanic Stream is a large tail of neutral and ionized gas originating from tidal and hydrodynamical interactions between the Magellanic Clouds as they orbit the Milky Way (MW). It carries a significant gas reservoir that could impact the future evolution of the MW. Despite its importance, no direct observational constraints on the Stream’s distance have been previously published. In this study, we analyze Very Large Telescope/Ultraviolet and Visual Echelle Spectrograph spectra of five blue horizontal branch stars in the MW halo located at distances ranging from 13 to 56 kpc near two regions of the Stream (near Stream longitudes of –79 ^∘ and –98 ^∘ ), with the aim of detecting Ca ii and Na i absorption. No Ca ii or Na i absorption is detected at Stream velocities in any of the individual spectra or in higher signal-to-noise stacks of the spectra. The resulting limits on the Ca ii absorption are significantly lower than the Ca ii columns measured in the Stream along extragalactic sight lines. These nondetections establish a firm lower distance limit of 42 kpc for one region of the Stream. For the other region, we set a firm lower limit of 20 kpc and a tentative lower limit of 55 kpc from the most distant star, but deeper spectra are needed to confirm this. Our results provide the first observational constraints on the gaseous Stream’s distance.